China and Central and Eastern European Countries : Regional Networks, Global Supply Chain or International Competitors? - Fung, K.C.; Korhonen, Iikka; Li, Ke; Ng, Francis (2012)
China has become leading recipients of foreign direct investment (FDI). Meanwhile, an increasing share of global FDI is going to many Central and Eastern European countries (CEECs). What is the relationship between inward FDI of China and the CEECs? We conceptualize the relationship according to three alternative paradigms: (1) China and the CEECs each exist in its own regional production network, with no linkage between FDI flows into China and into CEECs; (2) China and the CEECs together comprise a global production network, so that China's FDI is positively related to CEECs' FDI; and (3) FDI into China is a substitute for FDI into the CEECs, with the correlation being negative. In this paper, we study empirical estimates of this issue for 15 CEECs for 1990-2004 using four different econometric approaches: FGLS with Random effects, FGLS with fixed effects, EC2SLS and GMM. The result supports the conclusion that China's inward FDI does not crowd out CEECs' inward FDI. In fact, it shows that in some regressions FDI flows in these two regions are moderately complementary. Our analysis also confirms the importance for FDI flows of determinants such as market size, degree of trade liberalization, labor quality and a healthy global FDI supply.